A geography of residents' worry about the disruptive effects of contaminated sites. (6th November 2018) - Prior, Jason Hugh; Gorman‐Murray, Andrew; McIntyre, Erica; Connon, Irena; Adams, Jon; Madden, Ben
Abstract: While the links between contaminated sites and adverse effects on human health and well‐being are being increasingly recognised, some argue that the magnitude of the health problem is inadequately addressed because it is largely invisible. Health geographies literature has sought to highlight this invisibility by focusing on the link between contaminated sites and health. This study adds to health geographies by presenting unique insights into the geography of residents' worry about the disruptive effect of environmental contamination on health and well‐being. It analyses a sample of residents ( n  = 485) living near 13 contaminated sites across Australia. Ordinal logistic regression analysis of closed‐format survey questions was combined with coding of open‐ended survey questions to reveal the geography of residents' worry about contamination from nearby sites. First, the study explores some of the main relationships between residents, their environs, and contaminants from nearby source sites, which determines their levels of worry: residents' demographics, residents' proximity to sites, contaminant boundaries and borders, and type of contaminant. Second, the study investigates how worry affects residents' health and well‐being, ranging from effects on their personal functioning through to their sense of ontological security, which depends in part upon their perceptions of contaminants' impacts. Despite having identified a range of diverse and negative effects of worry about contamination on residents, we found that worry for contamination can also prompt coping strategies and problem‐solving, reinforcing the need for more research on this subject.